The Influence of Good Corporate Governance on Risk Management Disclosure (Case Study on Telecommunication Companies) - Aena, Hidayatul; Sasanti, Elin Erlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the effect of good corporate governance elements on risk management disclosure in telecommunications companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. This study applies quantitative methods with panel data regression analysis using the fixed effects model (FEM). The results show that the size of the board of commissioners has a significantly negative impact on risk disclosure, while the size of the audit committee and company size have a significantly positive impact. In contrast, the proportion of independent commissioners and institutional ownership did not have a significant effect. The findings findings provide recommendations to improve good corporate governance practices and risk management in telecommunication companies.